Hybrid System of Distributed Automation - Quintanova, André Bernardo (2019)
One of the most important tendencies in the development of the industrial automation is the application of intelligent control systems within factories, which focuses heavily on networked architectures. Following this line of thinking, the goal of this dissertation resumes itself in the implementation of a distributed system that controls two physical processes, where the system components not only trade information between each other, but also have that same information be accessible remotely and within HMI equipment. The controllers were conceptualized to offer different functional modes with high customization available. This system also takes resource of an OPC server, so it allows, not only the communication between different manufacturer PLC controllers but also the connection with remotes clients The implemented remote clients hold the intent of demonstrating the versatility of this architecture and are, namely, an operational historian that registers information and a data viewer, which allows the use of more advanced methods of monitoring.